A randomized controlled trial investigating the effects of celecoxib in patients with localized prostate cancer. - Sooriakumaran, P; Coley, H; Fox, S; Macanas-Pirard, P; Lovell, D; Henderson, A; Eden, C; Miller, P; Langley, SE; Laing, R (2009)
UNLABELLED: Cyclooxygenase-2 (COX-2) is associated with tumour promotion, inhibition of apoptosis, angiogenesis and metastasis. Celecoxib, a selective COX-2 inhibitor was investigated, in patients with clinically localized prostate cancer using immunohistochemistry. PATIENTS AND METHODS: Patients with cT1-2 prostate cancer (n=45) were randomized to celecoxib 400mg b.d. or no treatment for four weeks prior to radical prostatectomy. Histological sections of preoperative biopsy and matched radical prostatectomy specimens were stained for markers of cell proliferation (MIB-1/Ki-67), microvessel density (CD-31 with Weidner scoring), COX-2, apoptosis (TUNEL analysis), angiogenic factors (VEGF and KDR) and HIF-1. RESULTS: Celecoxib decreased tumour cell proliferation, microvessel density, angiogenesis and HIF-1 whilst enhancing apoptosis. These effects approached statistical significance in a multivariate model and the cell proliferation index approached statistical significance on univariate analysis. CONCLUSION: In this pilot study a 4 week regimen of celecoxib resulted in measurable biological effects in prostate cancer tissue. These findings warrant further investigation.